Effect of Ssd Vs Hdd Selection on Computer Boot Speed - Sonny R. Kasenda; Hizkia Pivel Lumi; Lovejoy Virrendra Wawointana; Rivq Kohongia; Lorensius Farel Sabonbaly; Revalina Putri Djafar (Syntax Corporation Indonesia, 2024)
This article aims to analyse the effect of SSD (Solid State Drive) and HDD (Hard Disk Drive) selection on computer boot speed. With the development of data storage technology, many computer users are faced with the choice between SSD and HDD. This research will compare these two storage media in terms of operating system boot performance, with the aim of providing a more appropriate recommendation based on the measured performance. This research is conducted by experimenting on two computers, one that uses SSD and one that uses HDD. Each computer will be tested by booting the same operating system under similar conditions. The boot speed is measured in seconds from the start of the computer until the operating system is ready for use. In addition, special software is used to measure the boot time with high accuracy. The results show that computers with SSDs have much faster boot speeds compared to HDDs. On average, SSDs can complete the boot process in 12-15 seconds, while HDDs take around 30-34 seconds. In addition, the boot time variability of SSDs is lower, indicating a more stable performance compared to HDDs. Based on the test results, it can be concluded that the use of SSD significantly improves the boot speed of a computer compared to HDD. Users who want faster system performance, especially in terms of boot time, are recommended to use SSD.